2007
DOI: 10.1097/01.tp.0000282805.33658.ce
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Standardized Nonsurgical Therapy in the Management of Biliary Anastomotic Strictures Complicating Liver Transplantation

Abstract: Endoscopic balloon dilatation and stenting is a safe and effective means of treating biliary anastomotic strictures complicating liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 20 publications
7
60
0
5
Order By: Relevance
“…Even 1 week before ERC diagnosis of AS, 96% of patients revealed a normal ultrasound (9). However, in a newer series 92% of patients with biliary complications revealed ultrasound abnormalities (10). Hepatic artery thrombosis (HAT)-or stenosis is excluded by additional Doppler examination.…”
Section: Diagnosis Of Biliary Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even 1 week before ERC diagnosis of AS, 96% of patients revealed a normal ultrasound (9). However, in a newer series 92% of patients with biliary complications revealed ultrasound abnormalities (10). Hepatic artery thrombosis (HAT)-or stenosis is excluded by additional Doppler examination.…”
Section: Diagnosis Of Biliary Complicationsmentioning
confidence: 99%
“…Early conversion to surgical therapy is indicated, since delay might be accompanied with persistent allograft dysfunction (45). In the long term, about 10-20% of patients with AS require surgical revision (10,18), mainly in the form of bilioenteric anastomosis (46,47). In most centers surgical treatment is regarded as second-line therapy and it has been shown, that previous failure of interventional therapy does no negatively affect the outcome after 'second-line' surgical reconstruction (48).…”
Section: Therapy Of Anastomotic Stenosismentioning
confidence: 99%
“…It is also advised that balloon dilation should not be performed for very early strictures and for strictures in the setting of an anastomotic leak to prevent disintegration of biliary anastomosis. Severe complications of this technique are rare, although, a large study showed a complication rate of 6.6% per procedure which increases to 21% per patient as they get more than one procedure [41] . Some of the complications include pancreatitis, cholangitis, stent migration and hemorrhage.…”
Section: Biliary Stricturesmentioning
confidence: 99%
“…The first plastic stent can be inserted either transhepatically or by a rendezvous transpapillary technique. The disadvantage of the single transhepatic technique is that it does not enable to insert multiple stents in one session (Holt et al, 2007;Pasha et al, 2007;Kulaksiz et al, 2008). …”
Section: Anastomotic Stricturesmentioning
confidence: 99%